Artificial pathway emergence in central metabolism from three recursive phosphoketolase reactions. (10th November 2018) - Krüsemann, Jan L.; Lindner, Steffen N.; Dempfle, Marian; Widmer, Julian; Arrivault, Stephanie; Debacker, Marine; He, Hai; Kubis, Armin; Chayot, Romain; Anissimova, Macha; Marlière, Philippe; Cotton, Charles A. R.; et al.
Abstract : The promiscuous activities of a recursive, generalist enzyme provide raw material for the emergence of metabolic pathways. Here, we use a synthetic biology approach to recreate such an evolutionary setup in central metabolism and explore how cellular physiology adjusts to enable recursive catalysis. We generate an Escherichia coli strain deleted in transketolase and glucose 6‐phosphate dehydrogenase, effectively eliminating the native pentose phosphate pathway. We demonstrate that the overexpression of phosphoketolase restores prototrophic growth by catalyzing three consecutive reactions, cleaving xylulose 5‐phosphate, fructose 6‐phosphate, and, notably, sedoheptulose 7‐phosphate. We find that the activity of the resulting synthetic pathway becomes possible due to the recalibration of steady‐state concentrations of key metabolites, such that the in vivo cleavage rates of all three phosphoketolase substrates are similar. This study demonstrates our ability to rewrite one of nature's most conserved pathways and provides insight into the flexibility of cellular metabolism during pathway emergence. Abstract : Recursive activities of generalist enzymes provide raw material for the emergence of pathways. We use synthetic biology to recreate this evolutionary setup, demonstrating that phosphoketolase restores growth of a strain deleted in the pentose phosphate pathway, by catalyzing three consecutive phosphosugar cleavage reactions. The observed adaptation of metabolite concentrations provides insight into the flexibility of cellular metabolism during pathway emergence.